0.6(x-1)+0.2=6.6

Simple and best practice solution for 0.6(x-1)+0.2=6.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6(x-1)+0.2=6.6 equation:


Simplifying
0.6(x + -1) + 0.2 = 6.6

Reorder the terms:
0.6(-1 + x) + 0.2 = 6.6
(-1 * 0.6 + x * 0.6) + 0.2 = 6.6
(-0.6 + 0.6x) + 0.2 = 6.6

Reorder the terms:
-0.6 + 0.2 + 0.6x = 6.6

Combine like terms: -0.6 + 0.2 = -0.4
-0.4 + 0.6x = 6.6

Solving
-0.4 + 0.6x = 6.6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.4' to each side of the equation.
-0.4 + 0.4 + 0.6x = 6.6 + 0.4

Combine like terms: -0.4 + 0.4 = 0.0
0.0 + 0.6x = 6.6 + 0.4
0.6x = 6.6 + 0.4

Combine like terms: 6.6 + 0.4 = 7
0.6x = 7

Divide each side by '0.6'.
x = 11.66666667

Simplifying
x = 11.66666667

See similar equations:

| -8(y-8)=2y-36 | | 2x-3=4-5x | | (6x^2+8x+12)-(4x^2+3x-2)= | | (3a^2-9a)+(12a^2+5a)= | | 13y-4y=27 | | (2+x)=(x*2) | | 2a+8=7a-5 | | 2.5*2x= | | 0.5x+12.3=7.1-1.1x | | (9x^2+6x+3)+(4x^2-8x+4)= | | 6c^2+21c-4c-14= | | (x+2)2+(y-6)2=25 | | 2x^2+5*2x= | | 3a(5a^2+8a)= | | -5x+7=3x+7 | | 14=6(y-2)+7y | | 6w+2(w+7)=30 | | 25+4y-1=16y-11-5y | | 4x+2y+z=166 | | 3+9x=7x+7-8 | | 5(u-3)-8u=-12 | | 108=LW | | -18n+12=-17n-14 | | A=15*12 | | -3x-10=5x+30 | | (-5xy)(2xy^2)= | | -4x-8=7 | | q/9=7/5 | | 10/7=5w | | 273729=72292 | | 8x^4-8= | | 7x+2y=20000 |

Equations solver categories